2004
DOI: 10.1063/1.1792091
|View full text |Cite
|
Sign up to set email alerts
|

The role of the reaction force to characterize local specific interactions that activate the intramolecular proton transfers in DNA basis

Abstract: MP2/6-311G** and B3LYP/6-311G** studies of the intramolecular proton transfer in adenine, cytosine, guanine, and thymine has been performed, with the aim of evaluating the role of the reaction force as a global descriptor of the process. It turns out that the reaction force profile is quite an interesting tool to characterize reaction mechanisms. Indeed, in adenine and cytosine the proton transfer is assisted by an increasing electronic delocalization in the adjacent ring, whereas in guanine and thymine the at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 22 publications
1
97
0
Order By: Relevance
“…The dissociation of a bond XY is divided by the minimum of F ( R c ) into two phases, as seen in Figure 2(b). These can be interpreted in terms of what was observed earlier 1–7 for processes having V ( R c ) and F ( R c ) profiles such as those in Figure 1. The first phase, as the bond is being stretched from R c = R e to R c = α, is characterized by a growing (negative) restoring force.…”
Section: Discussion and Summarysupporting
confidence: 80%
See 3 more Smart Citations
“…The dissociation of a bond XY is divided by the minimum of F ( R c ) into two phases, as seen in Figure 2(b). These can be interpreted in terms of what was observed earlier 1–7 for processes having V ( R c ) and F ( R c ) profiles such as those in Figure 1. The first phase, as the bond is being stretched from R c = R e to R c = α, is characterized by a growing (negative) restoring force.…”
Section: Discussion and Summarysupporting
confidence: 80%
“…The reaction force F ( R c ) that is associated with any chemical or physical process A → B can provide considerable insight into its mechanism. This has been demonstrated for a series of chemical reactions and conformational transformations 1–7, all of them characterized by energy barriers in both the forward and reverse directions. We shall now address the dissociation or formation of an individual bond, having a barrier in only one direction.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The existence of these molecules in many tautomeric forms has been revealed to be crucial to explain the mutation occurring during DNA duplication. 6 These tautomeric structures can be obtained through intramolecular hydrogen transfer in the monomeric structure [6][7][8] or by intermolecular hydrogen transfer in the dimer system formation. 9 Recently it has been shown that the intramolecular tautomerization of the monomeric structures of 2,4-diketo and 2-thio,4-keto uracil present quite high energy barriers of about 40 kcal/mol, so we explore in this article the way to obtain the enol or thiol tautomers from the intermolecular proton transfer reactions of dimeric structures of uracil and 2-thiouracil.…”
Section: Introductionmentioning
confidence: 99%